2022
DOI: 10.1158/2159-8290.cd-22-0287
|View full text |Cite
|
Sign up to set email alerts
|

Serial Profiling of Circulating Tumor DNA Identifies Dynamic Evolution of Clinically Actionable Genomic Alterations in High-Risk Neuroblastoma

Abstract: Neuroblastoma evolution, heterogeneity, and resistance remain inadequately defined, suggesting a role for circulating tumor DNA (ctDNA) sequencing. To define the utility of ctDNA profiling in neuroblastoma, 167 blood samples from 48 high-risk patients were evaluated for ctDNA using comprehensive genomic profiling. At least one pathogenic genomic alteration was identified in 56% of samples from 73% of evaluable patients, including clinically actionable ALK and RAS-MAPK pathway variants. Fifteen patients receive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 66 publications
2
18
0
Order By: Relevance
“…In comparison to other pediatric solid tumors, patients with neuroblastoma have significantly higher amounts of cfDNA circulating in plasma 36 . Additionally, our prior work and that of others have demonstrated that tumor-specific alterations can be monitored during the course of therapy through cfDNA surveillance and that cfDNA profiling captures dynamic tumor evolution in a way not possible with standard tumor biopsies 13,37,38 . Importantly, in the current study we demonstrated that a comparison of cfDNA and diagnostic tumor derived 5-hmC profiles identified a set of differentially hydroxymethylated genes associated with worse clinical outcome, supporting the hypothesis that cfDNA samples are enriched for DNA from the most aggressive, rapidly dividing tumor cells.…”
Section: Discussionmentioning
confidence: 96%
“…In comparison to other pediatric solid tumors, patients with neuroblastoma have significantly higher amounts of cfDNA circulating in plasma 36 . Additionally, our prior work and that of others have demonstrated that tumor-specific alterations can be monitored during the course of therapy through cfDNA surveillance and that cfDNA profiling captures dynamic tumor evolution in a way not possible with standard tumor biopsies 13,37,38 . Importantly, in the current study we demonstrated that a comparison of cfDNA and diagnostic tumor derived 5-hmC profiles identified a set of differentially hydroxymethylated genes associated with worse clinical outcome, supporting the hypothesis that cfDNA samples are enriched for DNA from the most aggressive, rapidly dividing tumor cells.…”
Section: Discussionmentioning
confidence: 96%
“…We, therefore, collected research-based serial ctDNA to characterize genomic changes in response to therapy, detect early disease progression and identify evolving alterations driving tumor heterogeneity and lorlatinib resistance. This same assay has already informed on the genetic evolution of relapsed neuroblastoma for patients not on this trial 46 . The full landscape of ctDNA genomic alterations in patients with ALK-driven refractory or relapsed neuroblastoma treated on this trial is detailed in a companion manuscript.…”
Section: Discussionmentioning
confidence: 98%
“…More recently, Lodrini et al., showed the applicability of detecting tumor-derived cfDNA MYCN and ALK copy number alterations and ALK hotspot mutations in longitudinal plasma samples from patients with neuroblastoma ( 30 ). The study of Bosse et al., that predominantly included neuroblastoma patients with an event (91%), showed at least one pathogenic genomic alteration detected in 56% of the samples ( 31 ). However, only 20% and 10% of neuroblastoma tumors harbor MYCN amplification or ALK mutation, respectively ( 4 ).…”
Section: Discussionmentioning
confidence: 99%